Managing the Neck in the Era of the Short Scar Face-Lift - Fedok, Fred G.; Sedgh, Jacob (Facial Plastic Surgery, 2012)
A recent trend in rhytidectomy has included the introduction of various short incision techniques, particularly the S-lift, the minimal access cranial suspension lift, and other short scar methods. However, this trend has not been without a criticism that these minimally invasive techniques might be limited in what might be achievable by such surgery. As with more traditional face-lift surgery, the management of the neck often presents as the most challenging aspect of the procedure when using short scar techniques. This article will present a brief history of cervical rhytidectomy and relevant surgical anatomy, as well as the authors' algorithmic approach to surgical assessment and management of the neck, the short incision operative techniques, and potential complications. In the authors' experience, attention to both the selection criteria and operative modifications in the execution of short scar techniques are critical to optimizing outcomes in cervical rejuvenation.
Keywords: SMAS: superficial musculoaponeurotic system; MACS: minimal access cranial suspension; short scar rhytidectomy; cervical rhytidectomy; neck-lift